2020
DOI: 10.1002/vjch.201900158
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical properties of amoxicillin on an economical, simple graphite pencil electrode and the ability of the electrode in amoxicillin detection

Abstract: Amoxicillin (AMX), an antibiotic in the class of beta-lactam antibiotics has shown an ability of adsorption onto the economical, simple graphite pencil electrode (GPE) and could be electrochemical oxidation. The oxidation peak signal of AMX on the treated electrode is better than the one on the original GPE that is in agreement with the increase of redoxidation peaks of Fe(II)/Fe(III) system when using treated electrode. The square wave Voltammetric signals of AMX have exhibited a direct proportion to AMX conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Sometimes, the graphite lead electrode is polished with an alumina slurry [25,41,47,59,67], on sandpaper with different granulometrics [40,42,68], on emery paper [41,[49][50][51][52]69] followed by a butter sheet [16,45], on butter paper [39], or on weighing paper [20,57,58,62,70]. Yen et al [71] reported that amoxicicllin presented a better electrochemical response at the PGE mechanically treated with polishing paper in comparison with the original electrode.…”
Section: Pge Manufacturing Proceduresmentioning
confidence: 99%
“…Sometimes, the graphite lead electrode is polished with an alumina slurry [25,41,47,59,67], on sandpaper with different granulometrics [40,42,68], on emery paper [41,[49][50][51][52]69] followed by a butter sheet [16,45], on butter paper [39], or on weighing paper [20,57,58,62,70]. Yen et al [71] reported that amoxicicllin presented a better electrochemical response at the PGE mechanically treated with polishing paper in comparison with the original electrode.…”
Section: Pge Manufacturing Proceduresmentioning
confidence: 99%
“…Amoxicillin is used to treat various types of bacterial infections, for example pneumonia, pneumonia, and urinary tract infection, since it has the capability to inhibit the synthesis of bacterial cell walls [ 13 ]. Spectrophotometric [ [14] , [15] , [16] , [17] ], chromatographic [ [18] , [19] , [20] ] and electrochemical [ 21 , 22 ] techniques are among several methods reported for determining this drug in pharmaceutical preparations. Whilst current techniques are highly accurate and sensitive in general they fail to achieve the criteria of being low cost, rapid, or easy to operate that are required for high throughput screening [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Amoxicillin (AMX), is an acid-stable, semi-synthetic drug that belongs to penicillin class of β-lactam antibiotics [ 3 ]. AMX, which is one of the vital medications recognized by the World Health Organization (WHO) [ 4 ], is a widely used antibiotic in human and veterinary medicine for the treatment and prevention of respiratory, gastrointestinal, urinary, and skin bacterial infections [ 5 , 6 ]. AMX ( Scheme 1 ) is the only phenolic penicillin and spectrum β-lactam antibiotic [ 7 ] and better absorbed following its oral administration being the choice of the β-lactam antibiotics [ 8 ], its improper usage may lead to side effects such as stomach pains, diarrhea, chills, and blood in the urine [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%